Social Justice Values in Islamic Education From The Perspective of Muhammad Zainuddin Abdul Majid - Kalsum, Umi; Munir, Munir; Nurlaila, Nurlaila (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
Social justice in Islamic education encompasses principles that ensure every individual receives equal rights to quality education, without discrimination based on social, economic, or ethnic status. This concept is the goal and ideal of Tuan Guru Muhammad Zainuddin Abdul Majid. This study aims to identify and analyze the values of social justice integrated by Mr. Zainuddin Abdul Majid in the field of education. The type of research is library research, using a qualitative approach. Data was collected through a review of primary books and previous scientific works, then analyzed to identify the integration of social justice values in the thoughts of Tuan Guru Muhammad Zainuddin Abdul Majid. The results of the study indicate that the educational development carried out by Tuan Guru Muhammad Zainuddin Abdul Majid in West Nusa Tenggara reflects the integration of social justice values as stated in the Preamble of the 1945 Constitution. Equal access to education is a right of all Indonesian citizens, as stipulated in the constitution, to achieve social justice for all Indonesian people. This study encourages the development of inclusive and equitable education policies that adopt the social justice values of Muhammad Zainuddin Abdul Majid.